Rome and the Roman Empire - Bailliot, Magali (2019)
This chapter follows the evolution of Roman juridical views on formulas and gestures thought capable of modifying the natural course of events. First, it considers the malum carmen and veneficium, criminalized in the Twelve Tables and Lex Corneilia. Both terms appear ambiguous in contemporaneous sources, yet they were proscribed in the legal codes, prompting Romans to develop various strategies to protect against them. The chapter also looks at the more ambiguous defixio, demonstrating how one can gain by investigating practices on their own terms.